Especialização em estratégia saúde da família : instrumento de transformação da prática profissional - Mattedi, Juliane Pereira Pimenta (2015)
Discussions on Continuing Education in Health intensified after the institutionalization of the Unified Health System (SUS) aiming to develop the professional valuation policies for SUS principles could reflect the quality of care. Many initiatives have been undertaken in the meantime, many of the specialized courses format. This paper analyzes the Specialization Course in Family Health Strategy (ESF), administered by the Federal University of Espirito Santo (UFES) in partnership with the City Department of Health Vitoria (SEMUS) in 2010-2011, contributed to change professional practice in the Family Health Units (USF) of Vitoria/ES. The study is descriptive and qualitative approach. For this there were three sessions focus group with the participation of 16 graduates of the course of deferent professional categories and different health units. The data show that after the course there were changes both personal and a professional, such as teamwork, knowledge of their skills in the ESF, exchange of experiences, link with other teams of the health system and strengthening the principles of ESF. On the other hand, reported that there are major obstacles to put fully into practice many of the course content, such difficulties are related to the work organization in USF, such as the requirement for productivity, training of professionals based on the traditional biomedical model and the distance between the daily lives of USF and the principles governing the ESF.